THE INFLUENCE OF TEACHING MATERIALS DEVELOPMENT ON STUDENT UNDERSTANDING IN CLASS VII ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT IT MIDDLE SCHOOL. AN-NAFIS TELUK MENGKUDU DISTRICT SERDANG BEDAGAI DISTRICT - Chairuddin Siregar; Irdian Ningsih (RADJA PUBLIKA, 2022)
This research uses a quantitative approach, where the symptoms are measured using numbers. The results of the research in this thesis, There is a significant positive relationship between the development of teaching materials on students' understanding of class VII Islamic Education subjects. This is evidenced by the results obtained, namely by using the product moment correlation formula, the correlation index value is obtained of 0.808 which ranges from 0.70 to 0.90, this means that there is a significant correlation between variable X and variable Y, namely a strong or high correlation. Then by examining the table of the value of